An Early Description of a "Human Mosaic" Involving the Skin: A Story from 1945 - Rudolf Happle (Medical Journals Sweden, 2020)
In 1945, the Journal of Heredity published an impressive article entitled "A human mosaic: bilaterally asymmetrical noevus pigmentosus pilosus et mollusciformis unilateralis." The author was M. Zlotnikoff, a Russian physician working in Ivanovo, a city located approximately 250 km northeast of Moscow. Zlotnikoff described a 24-year-old woman with a congenital linear epidermal naevus in a systematized and strictly unilateral arrangement. For the first time, the author explained this disorder as a mosaic resulting from a somatic mutation that occurred at an early stage of embryonic development. However, because this article was published immediately after the war, it fell into oblivion, despite the fact that it was of utmost importance in clinical dermatology. Zlotnikoff's work is all the more remarkable as the author had never heard of the lines of Blaschko.